Sensitivity to Moral Principles Predicts Both Deontological and Utilitarian Response Tendencies in Sacrificial Dilemmas. Issue 2 (March 2022) - Bostyn, Dries H.; Roets, A.; Conway, P.
When facing sacrificial dilemmas in which harm maximizes outcomes, people appear sensitive to three moral principles: They are more averse to actively causing harm than passively allowing it ( action principle ), causing harm directly than indirectly ( contact principle ), and causing harm as a means than as a by-product of helping others ( intention principle ). Across five studies and a meta-analysis ( N = 1, 218), we examined whether individual differences in people's sensitivity to these principles were related to participants' moral preferences on sacrificial dilemmas. Interestingly, sensitivity to each of these principles was related to both elevated harm-rejection (i.e., deontological) as well as elevated outcome-maximization (i.e., utilitarian) response tendencies. Rather than increasing responses consistent with only one philosophical position, people sensitive to moral principles balanced moral concerns about causing harm and maximizing outcomes similar to people high in other measures of moral concern.